Building Brand Engagement through Social Media Brandposts in Beauty Services - Samsurijal Hasan; Muh. Rezky Naim; Aryadi Aryadi; Librina Tria Putri (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Promotional activities are vital in marketing beauty services and should be factual, honest, informative, and educational. While advertising through conventional and digital media is common, social media offers a broader reach. Beautiful House Nitri in Bangkinang City, however, has limited use of social media for promotion despite targeting a digitally savvy community. Its official Facebook and Instagram accounts lack professional management, contributing little to marketing performance. This study aims to analyze brand engagement through social media by examining brand posts, comments, replies, likes, and shares on Beautiful House Nitri’s Facebook and Instagram accounts. Using content analysis, the research finds that Instagram outperforms Facebook in generating brand engagement, evidenced by higher consumer responses such as product reviews and user-generated content due to more active interactions. Beautiful House Nitri prioritizes Instagram and Facebook for information sharing and consumer interaction, posting mostly neutral brand posts and leveraging these platforms as responsive online customer care channels. The brand engagement achieved remains at the awareness stage, with informational brand posts designed to introduce beauty services and encourage users to follow its social media platforms.